Fluxnet Product from Storjarn, 2019-12-31–2023-12-31 - Matthias Peichl (Integrated Carbon Observation System, 2026)
Subset of half-hourly Fluxes and Meteo measurements processed with the international standard FLUXNET procedure (ONEFlux suite) for fast plotting purposes. Full data available in the Archive product.
Peichl, M. (2026). Fluxnet Product from Storjarn, 2019-12-31–2023-12-31, FLUXNET, https://hdl.handle.net/11676/5JT0sID4yvxlV7naifTmNtZ0
Keywords: Ecosystem Thematic Centre; carbon flux; pre-ICOS; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; quality flag (int); quality flag (int); incoming shortwave radiation; incoming shortwave radiation; incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; quality flag; quality flag; vapour pressure deficit; vapour pressure deficit; atmospheric pressure; atmospheric pressure; precipitation (total); precipitation (total); wind speed; wind speed; latent heat flux; latent heat flux; sensible heat flux; sensible heat flux; net ecosystem exchange; net ecosystem exchange; ecosystem respiration; ecosystem respiration; gross primary CO2 production; gross primary CO2 production; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap